A Rule based Approach for Anaphora Resolution in Bengali Sentences - Das, Angan; Banerjee, Abhishek; Maity, Samiya; Ranjan Pal, Alok (International Journal of Computer Sciences and Engineering, 2025)
Anaphora Resolution (AR) is one of the complex tasks in computational linguistics. It is the process of finding the referents in a given discourse. In this paper, anaphora resolution between a noun and its representative pronoun is presented using a rule-based model. First of all, a set of test sentences are retrieved from the Bengali text corpus. Each of the test sentences contains noun/s and its representative pronoun/s in it. Next, these sentences are processed using a set of rules to establish the relation between noun/s and its representative pronoun/s. The experiment is carried out on a set of 200 structured sentences and the overall accuracy is achieved 65.14%. The sentences are collected from the Bengali text corpus, developed in the TDIL (Technology Development for Indian Languages) project of the Government of India. The challenges and pitfalls of this work are described in this paper at last.